A new species of Silene (Caryophyllaceae) from Turkey - Özbek, Mehmet Ufuk; Uzunhi̇sarcikli Mehmet Erkan (Phytotaxa, 2019)
Silene arsuzensis Özbek & Uzunh. sp. nov. from Arsuz, Kale Village (Turkey, Hatay Province) is described and illustrated. It is morphologically similar to S. aegyptiaca from which differs in floral features (inflorescence, calyx and anthophore). A map of the new species and those of the species morphologically similar, as well as the ecological and biogeographycal remarks, conservation status, pollen and seed morphology are also presented.